2019
DOI: 10.1111/codi.14720
|View full text |Cite
|
Sign up to set email alerts
|

The LAPLAP study: a randomized placebo‐controlled clinical trial assessing postoperative functional recovery using intraperitoneal local anaesthetic in laparoscopic colorectal surgery

Abstract: Aim Postoperative pain remains a major factor in recovery from colorectal resection. There is increasing interest in opioid‐sparing analgesia, and intraperitoneal local anaesthetic (IPLA) has recently been shown to be useful in minor laparoscopic and open colorectal procedures. The aim of this study was to evaluate the impact of IPLA on functional recovery following major laparoscopic surgery. In this controlled trial, mobility, as measured by the De Morton Mobility Index (DEMMI), was used as a surrogate for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…The results of the search strategy are presented in figure 1. Thirteen studies meeting inclusion criteria for colorectal surgery and successful ERAS were included,37–49 comprising a total of 1170 patients, with variable methodological quality (figure 2). Only two studies (15.4%) were scored as low risk of bias in all domains 37 38.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the search strategy are presented in figure 1. Thirteen studies meeting inclusion criteria for colorectal surgery and successful ERAS were included,37–49 comprising a total of 1170 patients, with variable methodological quality (figure 2). Only two studies (15.4%) were scored as low risk of bias in all domains 37 38.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies meeting inclusion criteria for colorectal surgery and successful ERAS were included,37–49 comprising a total of 1170 patients, with variable methodological quality (figure 2). Only two studies (15.4%) were scored as low risk of bias in all domains 37 38. The characteristics of included studies are summarized in online supplemental table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,23 IPLA may have a lower rate of adverse effects including local anesthetic systemic toxicity due to reduced systemic absorption and a high first pass metabolism. 24 This is what allows for the utilization of less cardiotoxic and longer acting local anesthetics. 6 After a bolus of IPLA the levels increase in the blood stream with a mean Cmax of 1.01 to 4.32 mg/mL and a Tmax of 15 to 40 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of laparoscopic procedures in the treatment of colorectal cancer, numerous papers on this topic have been published. They showed an improvement in the quality of operative technique, and especially an advantage in the early postoperative recovery after this type of operative treatment [3,4,5]. The very beginning laparoscopically assisted colorectal surgery was promising, studies were done that confirmed that this type of surgery was less traumatic than open surgery.…”
Section: Discusionmentioning
confidence: 99%